Kecak Dance as A Medium of Cultural Diplomacy Between Indonesia and Japan 2024 - Arya Tirta Suardi; Gunawan Undang (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
This study examines the role of the kecak dance as a tool of Indonesian cultural diplomacy in bilateral relations with Japan in 2024. The focus is on the kecak dance performance at the Tokyo Fuji Art Museum as a means of introducing Indonesian culture. Using a descriptive qualitative method, this study found that the kecak dance functions as a cultural communication tool that builds a positive image of Indonesia in Japan. The Ministry of Foreign Affairs of the Republic of Indonesia and the Indonesian Embassy in Tokyo played an important role in supporting this initiative. Despite challenges such as limited budgets and differences in cultural perceptions, the opportunities that arise are considerable. In conclusion, the kecak dance has great potential in Indonesia's cultural diplomacy strategy in the future.